1996
DOI: 10.1089/jir.1996.16.1015
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Human Interferon-γ via Gene TransferIn Vitro:Prolonged Expression and Induction of Macrophage Antimicrobial Activity

Abstract: Daily parenteral administration of exogenous interferon-gamma (IFN-gamma) induces or accelerates recovery in experimental and human infections. To develop an alternative delivery system, a replication-defective recombinant adenovirus expressing human IFN-gamma was constructed. The complete coding region of IFN-gamma was amplified by RT-PCR and inserted into an adenovirus cloning vector under the control of a human cytomegalovirus promoter. Recombinant adenovirus containing the IFN-gamma minigene (dAv-IFN-gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As in the case of berylliosis, the chronic lung in¯ammation is related to HLA-DP genetics and not to the extent to which workers were exposed to beryllium. 40 The present study suggests that Sb exposure may suppress host defense against infectious microorganisms, because IFNg, a major cytokine mediating cell-mediated immune responses for the clearance of infectious pathogens, 41 was signi®cantly lowered in the Group A Sb-exposed workers (Figure 3). Furthermore, the Group B subjects also showed lower IFNg levels than Group C. According to the urine Sb levels (Table 1), Group B intra-factory control subjects were indirectly exposed to Sb although to a signi®cantly lesser degree than the Group A workers.…”
Section: Discussionmentioning
confidence: 67%
“…As in the case of berylliosis, the chronic lung in¯ammation is related to HLA-DP genetics and not to the extent to which workers were exposed to beryllium. 40 The present study suggests that Sb exposure may suppress host defense against infectious microorganisms, because IFNg, a major cytokine mediating cell-mediated immune responses for the clearance of infectious pathogens, 41 was signi®cantly lowered in the Group A Sb-exposed workers (Figure 3). Furthermore, the Group B subjects also showed lower IFNg levels than Group C. According to the urine Sb levels (Table 1), Group B intra-factory control subjects were indirectly exposed to Sb although to a signi®cantly lesser degree than the Group A workers.…”
Section: Discussionmentioning
confidence: 67%
“…2). Stoeckle et al (1996) [16] have demonstrated that human IFN-γ can be secreted in vitro by transfected HeLa cells and fibroblasts using a replication defective adenovirus for >4 weeks. To express caprine IFN-γ protein in COS-7 cells, Beyer et al (1998) [17] have used vectors containing CMV and caprine arthritis encephalitis virus long terminal repeat (CAEV LTR) promoters and employed Lipofectamine transfection method.…”
Section: Resultsmentioning
confidence: 99%
“…This process, termed transfection, can be accomplished using a number of vectors, which include viral vectors, polymers, and liposomes, and can be accomplished in vivo or in vitro 116. This approach has been used in numerous studies to obtain a sustained local IFN‐γ concentration 117–123. For example, Stoeckle et al have demonstrated in vitro that IFN‐γ can be secreted by transfected HeLa cells and fibroblasts using a replication‐defective adenovirus for > 4 weeks 120.…”
Section: Dosage Forms: Advantages and Limitationsmentioning
confidence: 99%
“…This approach has been used in numerous studies to obtain a sustained local IFN‐γ concentration 117–123. For example, Stoeckle et al have demonstrated in vitro that IFN‐γ can be secreted by transfected HeLa cells and fibroblasts using a replication‐defective adenovirus for > 4 weeks 120. The possible utility of the approach has also been demonstrated in Phase I clinical trials.…”
Section: Dosage Forms: Advantages and Limitationsmentioning
confidence: 99%